Peningkatan Kemampuan Kerjasama dan Keberanian Melalui Kegiatan Outbound di RA DWP UIN Sunan Kalijaga Yogyakarta - 'Aziz, Hafidh; Latif, Muhammad Abdul (PROGRAM STUDI PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD), FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2018)
This study aims to improve the ability of cooperation and courage of children through outbound activities in the A1 RA DWP group UIN Sunan Kalijaga Yogyakarta with 16 children, using classroom Kemmis and Mc Taggart model of action research with three cycles covering four stages, namely: planning, implementation, observation, and reflection. The results showed the ability of cooperation and courage of children had increased, (1) the ability of children cooperation before the action was  6.25%, in the first cycle it increased to 68.75%. In the second cycle increased by 6.25% to 75%. In the third cycle increased by 18.75% to 93.75%. (2) Child's courage ability before the action is 0%. In the first cycle it increased by 12.5%. In the second cycle, it increased by 62.5% to 75%, and in the third cycle it increased by 18.75% to 93.75%. (3) Implementation of outbound activities is able to improve the ability of cooperation and courage of children.